2019
DOI: 10.35808/ersj/1521
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Neuroscience Methods in the Analysis of the Impact of Advertisements in Shaping People's Health Habits*

Abstract: Purpose: The aim of the article is to present the use of selected techniques of cognitive neuroscience (EEG, GSR, HR) to study the effectiveness of social advertising in the context of promoting a healthy lifestyle. The respondents' reactions (emotions, remembering, interest) to individual fragments of the advertisement will be analyzed. The results of neural and psychophysiological measurements will be compared with the survey participants' answers provided in the survey (after the study with EEG, GSR, etc.).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Despite the fact that NeuroSky EEG has only a single channel, it has been prevalently used in many neuromarketing studies (Goode and Iwasa‐Madge, 2019; Hsu and Chen, 2019) for its reliability has been confirmed by scholars such as Rogers et al (2016), Sezer et al (2015), Chen and Huang (2013), and Rebolledo-Mendez et al (2009). It has also been proven to have sufficient accuracy in collecting brainwave oscillations, and the participants may not feel as awkward when wearing it (Sun, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that NeuroSky EEG has only a single channel, it has been prevalently used in many neuromarketing studies (Goode and Iwasa‐Madge, 2019; Hsu and Chen, 2019) for its reliability has been confirmed by scholars such as Rogers et al (2016), Sezer et al (2015), Chen and Huang (2013), and Rebolledo-Mendez et al (2009). It has also been proven to have sufficient accuracy in collecting brainwave oscillations, and the participants may not feel as awkward when wearing it (Sun, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…We advise studies future research using EEG on event-related potential in the field of hospitality and tourism to gain more insights into the minds of consumers when pushing the buy button in their brains, as 80% of buying behaviours are driven on an unconscious or subconscious level (Cuesta et al, 2020; Hafez, 2019; Morin, 2011). However, another fact remains that the effects engendered by subliminal stimuli can only last for a very short period of time (Ruch et al, 2016), and the long-term effects of these techniques are still in need of more empirical evidence. It has been suggested that EEG can be used in conjunction with other techniques such as facial electromyography (fMEG) (Li et al, 2015) or eye-tracking (Khushaba et al, 2012).…”
Section: Conclusion Implications and Limitationsmentioning
confidence: 99%
“…Therefore, we conclude that the changes in the activity of the skin are correlated with the changes in the activity of the brain. This investigation is novel in comparison to the published studies [1][2][3][4][5][6][7][8] that investigated the reaction of skin under different conditions without attempting to link it to brain activity.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the reported works, Galvanic Skin Response (GSR) signals are considered as the index of skin activity. The reported studies that evaluated GSR signals to analyze emotions [1,2] and stress [3,4], to identify driver distraction [5], to investigate the effectiveness of social advertising [6], to analyze the sleep quality of older adults [7], and to detect pain [8] are worthy of being mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Colomer Granero et al (2016) combined the aforementioned indices with GSR and HR measurements to classify advertisement spot into three categories (i.e., positive, neutral, and negative), with the use of the selected physiological features resulting in correct classification of the spot in nine out of ten times. Vecchiato et al (2014c), Piwowarski et al (2019), and Mateusz and Kesra (2020) examined the approach and withdrawal motivation alongside with emotional responses, working memory and attention. All three studies analyzed the physiological responses of EEG, GSR, and HR by formulating emotional, memorization and approach-withdrawal indices, with the scope of investigating the effectiveness of audiovisual advertisement.…”
Section: Advertisement Assessmentmentioning
confidence: 99%